TIME-VARYING PARAMETRIC REPRESENTATION OF SPEECH FOR MULTIMEDIA APPLICATIONS - A. A. Petrovsky; I. S. Azarov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Methods of time-varying speech parameterization for analysis, processing and synthesis in multimedia systems. The main theoretical points are given and practical issues are discussed. Some practical results of instantaneous pitch estimation and quality of voice morphing are presented.